THE EFFECTIVENESS OF MIND MAPPING TECHNIQUES IN COUNSELING OF ENHANCEMENT ABILITY MEMORY STUDENTS IN LEARNING - Irman Irman (Ta'dib, 2019)
This paper aims to explain the effectiveness of mind mapping techniques in counseling to improve students’ memory ability in learning. This research uses experimental design, especially pretest-posttest control group designs. The population of this research is the second semester students of Department of Islamic  Communication and Broadcasting of  FUAD IAIN Batusangkar Academic Year 2018/2019. The sample size was 12 students, consisting of an experimental group and a control group. Data analysis used independent t test through the SPSS computer program. release 20. The results of the study indicate that the mind mapping technique in counseling is effective in improving students' ability to remember lessons. These findings can be used as an alternative by lecturers and students to overcome students’ problems to remember the lessons in learning.